The Influence of Work Motivation and Leadership Style on Organizational Performance in the VUCA Era - Robi Mantik Tarliman; John Tampil Purba; Niko Sudibjo; Yohana F.C.P. Meilani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
In facing this VUCA era, organizations take into account that their Human Resources must be able to face the challenges of VUCA, one of which is mastering the skills needed to build and develop an organization in this VUCA era. The purpose of this study was to examine the effect of work motivation and leadership style on organizational performance in the VUCA era. The data collection technique uses a questionnaire with as many as 400 MSME leaders spread across various cities/regencies in West Java Province, namely Bogor Regency, Bandung Regency, Bandung City, Sukabumi Regency, Garut Regency, Cirebon Regency, Cianjur Regency, Karawang Regency, and Bekasi Regency. .. This type of research is quantitative with data analysis using Structural Equation Modeling(SEM). Based on the results of the analysis, the equation model Y = 0.88X1 + 0.26X2. The test results show that there is an influence of work motivation and leadership style on organizational performance in the VUCA era. This means the increased motivation and leadership style, the better the organizational performance significantly. Furthermore, when viewed from the determinant coefficient of 0.65, this coefficient shows that work motivation and leadership style variables contribute 65%, and the other 35% is explained by other factors outside of this research variable.